Design-Based Natural Disaster Education Practices for Primary School Teachers - Ahmet Oguz Akcay; Engin Karahan; Mehmet Arif Bozan; Feyzanur Ardic; Omer Garan (Journal of Education in Science, Environment and Health)
The goal of this study was to uncover primary teachers' perspectives on the use of design-based activities in disaster education and to thoroughly examine the plans. The study is designed as a case study. The participants were chosen using the purposeful sampling method. The study included 24 primary school teachers (12 male and 12 female) from various regions of the country. The data collection tools were group-prepared lesson plans and follow-up focus group interviews, which aimed to reveal their experiences and opinions on the lesson plan design process. The data was analyzed using the content analysis method. The findings revealed that the use of design-based activities in primary school, the importance of disaster education in the primary school curriculum, and the importance of disaster education awareness at the primary school level were all highlighted. The primary school teachers' lesson plans were examined, and the themes of drawing attention, design, material, career connections, and assessment-evaluation emerged. The significance of using design-based activities in primary schools, as well as the pedagogical benefits of using design-based activities in disaster education, was emphasized. Despite their abstract nature, natural disasters can be made more understandable through design-based education, particularly for primary school students who are in the concrete operational stage and have limited experience.